Deskripsi Kemampuan Komunikasi Matematis Ditinjau dari Tingkat Kemampuan Matematika Siswa SMA - Suradi Tahmir; Nasrullah; Sri Nurwana (Issues in Mathematics Education (IMED), 2020)
This research is a qualitative research with the aim of describing mathematical communication skills in terms of the level of mathematical ability of students in Senior High School to an understanding of trigonometric equations. There were 3 research subjects namely one student that has high-ability (KMT), one student that has medium-ability (KMS), and one student that has low-ability (KMR). The instruments used in data collection are written questions and interviews. This research shows that student with high mathematical abilities is able to write in detail the flow of problem solving, explain the solution correctly and systematically and be able to draw conclusions appropriately. In addition, students are also able to provide logical reasons for the steps to resolve the problem. Show that can be said that students are able to communicate the results of their work in detail. Student with moderate mathematical abilities still has errors and errors in solving problems, the reasons used in the settlement are sometimes still not correct and the writing of conclusions is still not in accordance with the command questions. So that it can be said that student is still unable to communicate the results of their work in detail. Student with low mathematical abilities tends to write down problem solving briefly, has not been able to draw conclusions from the solutions made and also has not been able to provide an explanation of the solutions made. This shows that student has not been able to communicate the results of their work.